2009
DOI: 10.1038/modpathol.2008.204
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial changes from short-term therapy with CDB-4124, a selective progesterone receptor modulator

Abstract: Selective progesterone receptor modulators are a class of drugs with progesterone antagonist activity that may confer therapeutic benefit for reproductive disorders in premenopausal women. Endometrial structure, which is dynamically controlled by circulating sex hormones, is likely to be perturbed by progesterone receptor modulators through their progesterone antagonist properties. We examined endometrial histology in 58 premenopausal women treated with the progesterone receptor modulator CDB-4124 (also known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 25 publications
(25 reference statements)
2
49
1
Order By: Relevance
“…The apparent relationship between mammary gland architecture and cyst formation that may have ductal or lobular origin is apparently a consequence of decreased functional activity of MECs as result of CDB-4124 treatment. This has also been observed in the endometrium of women treated for uterine fibroids and endometriosis with the same agent (30). The inhibitory effect of CDB-4124 on cell proliferation we see in both, long-and short-term (3 month) treatments correlates well with recent data from a clinical trial with mifepristone (RU-486).…”
Section: Discussion/conclusionsupporting
confidence: 73%
“…The apparent relationship between mammary gland architecture and cyst formation that may have ductal or lobular origin is apparently a consequence of decreased functional activity of MECs as result of CDB-4124 treatment. This has also been observed in the endometrium of women treated for uterine fibroids and endometriosis with the same agent (30). The inhibitory effect of CDB-4124 on cell proliferation we see in both, long-and short-term (3 month) treatments correlates well with recent data from a clinical trial with mifepristone (RU-486).…”
Section: Discussion/conclusionsupporting
confidence: 73%
“…At the same time, women on PRMs should retain tonic levels of estrogen in the absence of progesterone. While this might suggest the establishment of a state of unopposed estrogen, the direct effect of PRMs on the endometrium producing PAEC (Ioffe et al, 2009) avoids unopposed estrogenic stimulation.…”
Section: New Directionsmentioning
confidence: 99%
“…In a recent study 58 premenopausal women with endometriosis or uterine leiomyomas were treated for 3 or 6 months with different doses of CDB-4124. Endometrial biopsies were taken and were independently examined by 3 pathologists (Ioffe et al, 2009). They confirmed previous observations for cystic formations among endometrial glands and reported lack of endometrial hyperplasia or carcinomas in treated patients.…”
Section: Evidence For the Cellular Mode Of Action: Uterine Proliferatmentioning
confidence: 99%
“…More recently, an additional concern has emerged following histological evaluations of subjects dosed for more than 3 months on steroidal PRAs. The endometrium of these individuals undergoes a characteristic cystic histological change which may be difficult to distinguish from endometrial hyperplasia without specialist evaluation (Ioffe et al, 2009;Mutter et al, 2008;Williams et al, 2007).…”
Section: Discovery Of Small Molecule Modulators Of Pr Functionmentioning
confidence: 99%